(untitled) (Research, Society and Development, 2022)
Introduction: Tooth whitening is one of the most sought after procedures by patients in the dental office, which is mainly due to the “beauty standard” imposed by society, which requires white and aligned teeth. Driven by this, the search for the technique increases and its wide dissemination has made it one of the best known in the world. Objective: The objective of this work is to review the literature in order to understand which techniques are currently available to reduce dental sensitivity. Methodology: The present study consists of a literature review built from a survey of bibliographic sources. Results: Tooth whitening is a technique that dates back to antiquity, that is, for a long time, lighter teeth were desired and positively linked to the aesthetics of an individual. Results and Discussions: Currently, there are three techniques for bleaching teeth in vital teeth: at-home, in-office bleaching, and when you want to reduce bleaching time, the combination of the two techniques. In the office technique, hydrogen peroxide or carbamide is used in a concentration that varies from 35% to 40%. Conclusion: Despite the advance in knowledge through several researches available in the area, the main unwanted side effect, post-bleaching sensitivity, is still not completely elucidated, as well as ways to avoid the condition completely.